Intravenous thrombolysis in stroke with admission NIHSS score 0 or 1. Issue 1 (January 2022) - Sykora, Marek; Krebs, Stefan; Simader, Florentina; Gattringer, Thomas; Greisenegger, Stefan; Ferrari, Julia; Bernegger, Alexandra; Posekany, Alexandra; Lang, Wilfried
Background: Up to 30% of stroke patients initially presenting with non-disabling or mild deficits may experience poor functional outcome. Despite, intravenous thrombolysis remains controversial in this subgroup of stroke patients due to its uncertain risk benefit ratio. Aim: We aimed to analyze the real-world experience with intravenous thrombolysis in stroke patients presenting with very low NIHSS. Methods: Data of stroke patients presenting with mild initial stroke severity (NIHSS 0–5) including vascular risk factors, stroke syndrome and etiology, early neurological deterioration, symptomatic intracerebral haemorrhage (sICH), and functional outcome by modified Rankin Scale were extracted from a large nationwide stroke registry and analysed. Patients were categorized and compared according to admission severity NIHSS 0–1 versus NIHSS 2–5 and intravenous thrombolysis use. Results: Seven hundred and three (2%) of 35, 113 patients presenting with NIHSS 0–1 and 6316 (13.9%) of 45, 521 of patients presenting with NIHSS 2–5 underwent intravenous thrombolysis. In the NIHSS 0–1 group, intravenous thrombolysis was associated with early neurological deterioration (adjusted OR 8.84, CI 6.61–11.83), sICH (adjusted OR 9.32, CI 4.53–19.15) and lower rate of excellent outcome (mRS 0–1) at three months (adjusted OR 0.67, CI 0.5–0.9). In stroke patients with NIHSS 2–5, intravenous thrombolysis was associated with early neurological deterioration (adjusted OR 1.7, 1.47–1.98), sICH (adjusted OR 5.75, CI 4.45–7.45), and higher rate of excellent outcome (mRS 0–1) at three months (adjusted OR 1.21, CI 1.08–1.34). Conclusions: Among patients with NIHSS 0–1, intravenous thrombolysis did not increase the likelihood of excellent outcome. Moreover, potential signals of harm were observed. Further research seems to be warranted.